(untitled) (Janaki Medical College Journal of Medical Science, 2021)
Background and Objectives: The human being is found different by its overall morphology and body dimensions. Thus, the study was focussed to access the correlation of different facial measurements among undergraduate medical and nursing students in Nepal. Material and Methods: An institutional based cross-sectional study was carried out in the Department of Clinical Anatomy, Maharajgunj Medical Campus, Institute of Medicine, Kathmandu, Nepal. The variables selected for the present study was 140 subjects, among them 44 were female and 96 were male. Physical measurements were made by Spreading Caliper, Measuring tape, Weight machine, Height Scale. All the procedures were of non-invasive type. The personal height and weight, head length, head breadth, head circumference, Facial height, bigonial breadth, bizygomatic facial breadth was measured using International standard protocol. Statistical analysis was done using SPSS 20. ‘t’ tests was applied. P <0.05 was considered to be statistically significant. Results: Out of total, 68.6% were male and 31.4% were female. The mean age of the study participants were 20.36±1.29 ranges from 18 years to 26 years. The mean facial height and bizygomatic facial width of male were 10.96 cm and 13.64 cm with SD of 0.59 cm and 0.48 cm whereas for female the mean were 10.13 cm and 12.75 cm with SD of 0.67 cm and 0.49 cm respectively. The anthropometry and different facial measurements among males were significantly higher (p<0.0001) than the females. A positive correlation was observed for head breadth, head circumference, bigonial breadth, facial height, bizygomatic facial width whereas an inverse correlated was observed inversely correlated for head length with age. Conclusions: The anthropometry (height, weight, head length, head breadth, head circumference) and different facial measurements (Bigonial breadth, Bizygomatic facial width, and Facial height) among MBBS students were found to be significantly higher than the nursing students. A positive correlation was observed for head breadth, head circumference, bigonial breadth, facial height, bizygomatic facial width whereas an inverse correlated was observed inversely correlated for head length with age.